Stability Analysis of Distributed Order Fractional Chen System - H. Aminikhah; A. Refahi Sheikhani; H. Rezazadeh (The Scientific World Journal)
We first investigate sufficient and necessary conditions of stability of nonlinear distributed order fractional system and then we generalize the integer-order Chen system into the distributed order fractional domain. Based on the asymptotic stability theory of nonlinear distributed order fractional systems, the stability of distributed order fractional Chen system is discussed. In addition, we have found that chaos exists in the double fractional order Chen system. Numerical solutions are used to verify the analytical results.